Assessing an Interactive Online Tool to Support Parents' Genomic Testing Decisions. Issue 1 (14th December 2018) - Adam, Shelin; Birch, Patricia H.; Coe, Rachel R.; Bansback, Nick; Jones, Adrian L.; Connolly, Mary B.; Demos, Michelle K.; Toyota, Eric B.; Farrer, Matthew J.; Friedman, Jan M.
Abstract: Clinical use of genome‐wide sequencing (GWS) requires pre‐test genetic counseling, but the availability of genetic counseling is limited. We developed an interactive online decision‐support tool, DECIDE, to make genetic counseling, patient education, and decision support more readily available. We performed a non‐inferiority trial comparing DECIDE to standard genetic counseling to assess the clinical value of DECIDE for pre‐GWS counseling. One hundred and six parents considering GWS for their children with epilepsy were randomized to conventional genetic counseling or DECIDE. Following the intervention, we measured parents' knowledge and empowerment and asked their opinions about using DECIDE. Both DECIDE and conventional genetic counseling significantly increased parents' knowledge, with no difference between groups. Empowerment also increased but by less than 2% in each group. Parents liked using DECIDE and found it useful; 81% would recommend it to others; 49% wished to use it along with a genetic counselor; 26% of parents preferred to see a genetic counselor; 7% preferred DECIDE alone; and 18% had no preference. DECIDE appears equivalent to genetic counseling at conveying information. In addition, it was highly acceptable to the majority of study participants, many of whom indicated that it was useful to their decision‐making. Use of DECIDE as a pre‐test tool may extend genetic counseling resources. Abstract :